A LARGE SCALE SEISMIC MONITORING PARADIGM AND ACCELEROMETRY TECHNIQUE BASED ON THE GIANT MAGNETORESISTANCE EFFECT - Bukhari, M. H. S. (Malaysian Journal of Science, 2011)
An alternative paradigm in seismic monitoring is suggested and demonstrated here, incorporating a stratagem involving large-scale and multi-nodal monitoring using inexpensive sensors. A new seismic accelerometry method and its preliminary testing are reported here, based on the use of the Giant Magnetoresistance (GMR) effect (for the first time). The sensitivity, linearity and noise performance were observed to be satisfactory for the problem at hand, and the chosen magnitude of bias magnetic field was noted to effectively eliminate interference from the geomagnetic field. Analysis of obtained data reveals the technique as a viable method in seismic monitoring. It is proposed that a large array of such low-cost units could be valuable in a large seismically-active zone to monitor foreshock patterns, plate dynamics and developing defects, and could provide valuable insight for seismic monitoring.